HUBUNGAN TINGKAT KEBISINGAN LALULINTAS TERHADAP V/C RASIO DI SMA NEGERI 70 JAKARTA SAAT PANDEMI COVID-19 - Firas Ammar Tafri; Melati Ferianita Fachrul; Pramiati Purwaningrum (Universitas Trisakti, 2021)
Schools are educational facilities that must provide a sense of comfort and calm in learning activities. Noise can interfere with comfort and tranquility in learning activities. The source of school noise comes from traffic and other loud noises. Therefore, this study aims to determine the effect of traffic noise during the COVID-19 pandemic on the school environment of SMA Negeri 70 Jakarta and efforts to reduce noise levels in the school environment. Noise measurements were carried out for 14 days and carried out in the L1-L5 time segment which was carried out for 10 minutes with data reading every 5 seconds using a Sound Level Meter (SLM). The method used in determining the value of the traffic noise level is to measure the time and number of vehicles that pass through the measurement point along Jalan Raya Bulungan. From the results of the research at SMA Negeri 70 Jakarta, the noise level produced during the 14 days of the COVID-19 pandemic at SMA Negeri 70 Jakarta at points 1,2,3,5,7,8,9, and A exceeded the noise level quality standard. KepMenLH No. 48 of 1996 each has a value of 58.12 dBA; 56.18 dBA; 56.77 dBA; 56.55 dBA; 56.17 dBA; 60.10 dBA; 61.23 dBA; and 67.75 dBA. The V/C ratio at SMA Negeri 70 Jakarta shows the highest level of road service is on the 1st Sunday on Saturday, while the level of road service enters the class A category. At point A has the highest noise value of 67.75 dBA because it is located close to with a noise source, namely Jalan Raya Bulungan, while point 7 which is located far from the noise source has a noise level of 56.17 dBA.